Kinerja Pegawai pada Dinas Perpustakaan dan Kearsipan Daerah Kabupaten Barito Timur - Mahrini, Mahrini (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
The results of the study show that the performance of the employees of the East Barito Regency Library and Archives Office is quite optimal. First, the quality consisting of work results that are not yet effective due to the lack of expertise or their ability to work and for the suitability of the task is good because it is regulated by the duties and functions of each work section, Second, the quantity consisting of the time used to carry out tasks this is hampered by the lack of awareness or discipline in their work and the speed of this work is also disturbed by low expertise. Third, the implementation of tasks consisting of accurate work which is very good because it is supported by accurate data and compiled guidelines and for expertise is still lacking. Fourth, responsibility consisting of awareness that is still lacking about using working hours effectively and obligations that are not carried out professionally. Factors that influence are low expertise, employee indiscipline and lack of facilities and infrastructure. Efforts made First, improve work discipline, Second, provide work coaching, Third, provide work motivation, Fourth, clear work targets. Fifth, take a personal approach to employees. Sixth, provide reprimands or warnings for employees who violate the rules.